Efektivitas konseling psikoanalisa menggunakan teknik interpretasi terhadap perkembangan moral siswa SMP - Siti Mahmudah Amrul Khoiriah; Ni Ketut Suarni; Nyoman Dantes (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
The purpose of this study is to determine the effectiveness of the psychoanalysis counseling model interpretation techniques on the moral development of students, looking for the tendency of moral development of students of class VII Quba Foundation and apakah counseling psychoanalysis techniques interpretation effective in the moral development of students of Quba Foundation. This study is an experimental study with a pretest posttest design only one group design, the population in this study is the entire Quba Foundation Junior High School, theampelous of this study is 21 people consisting of grade VII junior high school students who were taken through purpose sampling techniques, the data collection etode uses a moral development questionnaire of 30 items that have met the internal test of item consistency and reliability in the high category. Based on prettest data where previously there were 10 students who had a high category, after receiving classical guidance treatment psychoanalysis counseling posttest data interpretation techniques showed very high category changes, it can be interpreted as the tendency of moral development of class VII students of the Quba Foundation after getting treatment has good skills. The empirical findings in this study are a psychoanalytic counseling model of effective interpretation techniques in the development of student morale. Based on the results of the hypothesis test, the SPSS output obtained a sig value of 0.01. Because the value of sig = 0.0 1 < 0.05, so it can be concluded that it is accepted that